2004
DOI: 10.1158/1078-0432.ccr-04-0054
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Absolute Counts of T Lymphocyte Subsets and Their Relation to Disease in Squamous Cell Carcinoma of the Head and Neck

Abstract: Results: Patients with SCCHN had significantly lower absolute numbers of CD3؉ CD4؉, and CD8؉ T cells than normal controls. However, no differences in the percentages of T-cell subsets between patients and normal controls were observed. Patients with active disease had significantly lower CD3؉ and CD4؉ T-cell counts than those with NED. Patients who had NED after surgery and radiotherapy had the lowest T-cell counts among the NED cohort. Patients who had NED for >2 years did not recover their T-cell counts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
202
5
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 238 publications
(225 citation statements)
references
References 20 publications
15
202
5
3
Order By: Relevance
“…We have previously reported a decrease in absolute CD4 þ T-cell counts in patients with SCCHN relative to age-matched NC (Kuss et al, 2004a). In the cohort of patients studied here, the mean absolute CD4 þ T-cell count was 6107350 mm À3 , which is significantly lower than the normal mean count of 10057360 mm 3 (Kuss et al, 2004a).…”
Section: Annexin V Binding To the Subsets Of Cd4 þ T Cellscontrasting
confidence: 57%
See 4 more Smart Citations
“…We have previously reported a decrease in absolute CD4 þ T-cell counts in patients with SCCHN relative to age-matched NC (Kuss et al, 2004a). In the cohort of patients studied here, the mean absolute CD4 þ T-cell count was 6107350 mm À3 , which is significantly lower than the normal mean count of 10057360 mm 3 (Kuss et al, 2004a).…”
Section: Annexin V Binding To the Subsets Of Cd4 þ T Cellscontrasting
confidence: 57%
“…The CD4 þ T-cell subset of lymphocytes was previously studied by us in patients with SCCHN Kuss et al, 2004a). We found that the absolute count of circulating CD4 þ T cells was significantly decreased in these patients (Kuss et al, 2004a).…”
mentioning
confidence: 61%
See 3 more Smart Citations